A Narrative Review on Biologic Joint Therapy in Chronic Bilateral Mandibular Luxation - Shahidi, Seyed Hossein; Ghasemzadeh, Sadaf; Zarehgar, Sayeh; Ghotbi, Nader; Bagherian, Fatemeh; Mahmoudi Anzabi, Reza; Mohammadikhah, Meysam; Ahangar Atashi, Nima (Galen Medical Journal, 2024)
Background: Temporomandibular joint (TMJ) luxation, or dislocation, is a relatively infrequent but highly consequential condition that requires prompt medical attention. This narrative review strives to offer a thorough summary of TMJ luxation treatment modalities, with a focus on recent advancements in biological treatments. Materials and Methods: A narrative review was conducted by synthesizing data from various sources, including systematic reviews, meta-analyses, and clinical trials. The review covers studies published up to 2024. Results: Various surgical techniques, such as eminectomy, midline mandibulotomy, and extended prosthetic total TMJ reconstruction (eTMJR), have been used to treat chronic TMJ dislocation. Platelet-rich plasma (PRP) and hyaluronic acid (HA) have shown promise in treating TMJ disorders. PRP can promote healing and reduce inflammation, while HA improves mandibular mobility and reduces pain. A combination of HA and PRP has been found to be particularly effective in treating TMJ disorders. Autologous blood injection (ABI) has been shown to be effective in reducing the recurrence of dislocation and improving patient outcomes, with fewer side effects compared to other treatments. Conclusion: TMJ luxation is a multifactorial condition that requires prompt and appropriate management to prevent long-term complications. While various surgical techniques are available, biological treatments such as PRP, HA, and ABI have shown promising results, particularly in reducing pain and improving joint function. Further research, including randomized controlled trials, is required to ascertain the most efficacious therapy modalities and to refine clinical guidelines for the management of TMJ luxation.